Radiotherapy induced dermatitis is a strong predictor for late fibrosis in head and neck cancer. The development of a predictive model for late fibrosis. Issue 2 (February 2017) - Nevens, Daan; Duprez, Fréderic; Daisne, Jean Francois; Laenen, Annouschka; De Neve, Wilfried; Nuyts, Sandra
Abstract: Purpose: To determine if the severity of radiodermatitis at the end of radio(chemo)therapy (R(C)T) for head and neck cancer (HNC) is a predictive factor for late fibrosis of the neck and to find a model to predict neck fibrosis grade ⩾ 2 (fibrosis RTOG2-4 ) at 6 months following R(C)T for HNC. Material/methods: 161 patients were prospectively included. We correlated radiodermatitis at the end of RCT, age, sex, T/N stage, tumor site, concomitant chemotherapy, upfront neck dissection, neo-adjuvant chemotherapy, accelerated RT, smoking, alcohol consumption, HPV status and the dose prescribed to the elective neck with fibrosis RTOG2-4 6 months after the end of treatment. Results: Radiodermatitis at the end of R(C)T ⩾grade 3 proved to be associated with the incidence of fibrosis RTOG2-4 at 6 months ( p  < 0.01). Furthermore, upfront neck dissection ( p  < 0.01), increasing N stage ( p  < 0.01) and tumor site ( p  = 0.02) are significantly associated in univariate analysis with fibrosis RTOG2-4 at 6 months of follow-up. Upfront neck dissection and radiodermatitis grade ⩾ 3 at the end of R(C)T were identified by our multivariate model. Additionally, increasing N stage was selected as an independent predictor variable. The AUC for this model was 0.92. Conclusion: A model for the prediction of fibrosis RTOG2-4 following R(C)T for head and neck cancer is presented with an AUC of 0.92. Interestingly, radiodermatitis grade ⩾ 3 at the end of R(C)T is associated with RTOG2-4 fibrosis at 6 months.